2007
DOI: 10.1007/s10103-007-0453-y
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes of enamel, dentin–enamel junction, and dentin induced by irradiating outer enamel surfaces with CO2 laser

Abstract: The microstructural changes of enamel, dentin-enamel junction (DEJ), and dentin after CO(2) laser irradiation were studied. Buccal enamel surfaces of human third molars about 2 mm from the DEJ were irradiated, and the laser tip was moved 5 mm in a mesiodistal direction with 5 s of irradiation time. The output powers were 2 to 10 W in a continuous mode, and the average doses were approximately from 250 to 1,250 J/cm(2). All specimens were examined by a scanning electron microscope, and heat-transfer simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 22 publications
0
16
0
4
Order By: Relevance
“…It produces a decrease in acid diffusion, and alterations in organic and inorganic components of the enamel lead to increased enamel microhardness and decreased enamel susceptibility to acid. 40 Also, Daniel et al showed that CO2 laser beam was effective in the reduction of mineral loss around composite resin filling on root surfaces and CO2 laser could be a resource in the prevention of secondary caries lesions on elderly population. 33 In the current study, CPP-ACP was used alone and in conjunction with laser to treat demineralized enamel lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It produces a decrease in acid diffusion, and alterations in organic and inorganic components of the enamel lead to increased enamel microhardness and decreased enamel susceptibility to acid. 40 Also, Daniel et al showed that CO2 laser beam was effective in the reduction of mineral loss around composite resin filling on root surfaces and CO2 laser could be a resource in the prevention of secondary caries lesions on elderly population. 33 In the current study, CPP-ACP was used alone and in conjunction with laser to treat demineralized enamel lesions.…”
Section: Discussionmentioning
confidence: 99%
“…24 In fact, the change caused by laser enhances the penetration of CCP-ACP nanocomplex into HA crystals in deeper layers. 40,45 Thus, it has higher efficacy than the application of laser or CPP-ACP alone for remineralization. …”
Section: Discussionmentioning
confidence: 99%
“…In [14] it was shown that the use of laser radiation both independently, and in combination with the use of fluoride, reduces enamel solubility in acid and increases its microhardness. It is Brought to you by | Stockholms Universitet Authenticated Download Date | 7/13/15 1:12 AM also noted that dentin structures become denser under the action of laser radiation at subthreshold energy den sities [15]. According to modern concepts, such effects in tissues appear to be due to local heating (from 100°C to 1100°C) which leads to structural, chemical and crystal line changes in tissues [16][17][18].…”
Section: Introductionmentioning
confidence: 95%
“…Outra provável explicação está na combinação de permeabilidade reduzida com menor solubilidade do substrato causada pela fusão e recristalização das microestruturas da superfície de esmalte (RODRIGUES et al, 2004;MOSHONOV et al, 2005;CHIANG et al, 2008). O conteúdo de água e carbonato do esmalte também foi descrito como reduzido quando a superfície foi irradiada com laser de CO 2 (McCORMACK et al,1995;PHAN et al, 1999).…”
Section: Discussionunclassified
“…A maior parte da luz é absorvida nos primeiros micrômetros externos da superfície do esmalte e convertida em calor (CHIANG et al, 2008). O efeito térmico do laser de CO 2 seria o responsável por aumentar a resistência do esmalte dental à ação dos ácidos (FOX et al, 1992;PHAN et al, 1999).…”
Section: Introductionunclassified